Neuroactive Steroids in Hypoxic–Ischemic Brain Injury: Overview and Future Directions - Toro Urrego, Nicolas (2020)
Hypoxic?ischemic brain injury is a number one cause of long-term neurologic dis- ability and death worldwide. This public health burden is mainly characterized by a decrease in oxygen concentration and blood flow to the tissues, which lead to an inef- ficient supply of nutrients to the brain. This condition induces cell death by energy depletion and increases free radical generation and inflammation. Hypoxic ischemic brain injury may occur in ischemic-stroke and over perinatal asphyxia, being both leading causes of morbidity in adults and children, respectively. Currently, there are no effective pharmaceutical strategies to prevent the triggering of secondary injury cascades, including oxidative stress and metabolic dysfunction. Neuroactive steroids like selective estrogen receptor modulators, SERMs, and selective tissue estrogenic activity regulators, STEARs, exert several neuroprotective effects. These encompass mitochondrial survival, a decrease in reactive oxygen species, and maintenance of cell viability, among others. In this context, these neurosteroids constitute promising molecules, which could modify brain response to injury. Here we show an updated overview of the underlying mechanisms of hypoxic ischemic brain injury. We also highlight the neuroprotective effects of neurosteroids and their future directions.